The woman in the role of judge in brazilian courts - Pires, Raísa Paiva (2023)
From the last decades of the 20th century, transformations occurred in the legal professions with the increase in the number of women, a phenomenon called “feminization”. In Latin America, there was an increase in the number of women in undergraduate courses in Law and entering public careers in the justice system, especially through public tenders. Legal careers were consolidated, by hegemony, from a male perspective. Thus, this research focuses on the entrance, career, difficulties and support experienced by women in the exercise of the position of judge, since the literature demonstrates that the increase in this participation is not linear over time and is not homogeneous in functions, areas of activity or positions. Thus, this work is justified due to the importance of constant evaluation of the social relations of work in the Brazilian courts, with the comparison of the latest data provided in commissions and the National Council of Justice reports. No articles were found on this subject published in scientific journals available in databases that calculate the impact factor. In this sense, given the lack of knowledge about women's performance, the conflicts and ambiguities of female judges' roles, this investigation is based on theoretical perspectives of social relations of work and gender that occur in the Brazilian Judiciary and on the phenomenon called glass ceiling, perspectives which contribute to the expansion of knowledge on the subject. The general objective of the study is to characterize and discuss the social relations of work and gender in the judicial career of female judges in Brazilian courts. For this, it was treated about social relations of gender and the performance of women in the labor market, in general, with the search for the state of the art of the theme. It was found that there are different barriers that women face in advancing and developing their careers, confirming the presence of prejudice in environments marked by male hegemony. The glass ceiling phenomenon was also addressed, which indicates the gender disparity in relation to women's access to management positions, given that most leadership and management positions are occupied by men. Several aspects interfere in this phenomenon, which is a product of factors that precede the promotion of women to high-ranking positions in organizations. In order to make it feasible to reach the proposed objectives, a qualitative and descriptive research was carried out. Primary data were collected through semi-structured interviews, carried out in October and November 2022, with 11 judges and 13 female judges from the five regions of Brazil, using Microsoft Teams. The Atlas T.I software was used to assist in data processing and, thus, 14 codes and four constructs were identified with the coding of important excerpts from the interviews: career entry and permanence; work-life balance; career and work; and leadership. The results show, in relation to women judges, barriers to entry and permanence in the career, difficulties in promotion due to merit, impacts of work on the family, prejudices, leadership issues, proposals for affirmative action for gender parity, among other factors, which were addressed at work. As a recommendation for improving judicial administration practices, it was found that the glass ceiling phenomenon should be better investigated, especially in the matter of promotion by merit to the position of judge. Even though the National Council of Justice defined objective criteria for promotion based on merit, such as performance scores and objective criteria for productivity and speed in the exercise of jurisdiction, all the judges interviewed pointed out interpersonal issues favorable to men in promotion.